Bulgaria : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2003)
This Report on the Observance of Standards and Codes Data Module provides a review of Bulgaria's data dissemination practices against the IMF's special data dissemination standard, complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. Bulgaria has adopted a restructuring program, aimed at stabilization and significant improvements in fiscal and monetary statistics. Bulgarian statistics have been relevant, consistent, and available on a timely basis with good frequency.